2022
DOI: 10.3390/ijms23158112
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine CXCL10 Modulates the Tumor Microenvironment of Fibrosis-Associated Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) constitutes a devastating health burden. Recently, tumor microenvironment-directed interventions have profoundly changed the landscape of HCC therapy. In the present study, the function of the chemokine CXCL10 during fibrosis-associated hepatocarcinogenesis was analyzed with specific focus on its impact in shaping the tumor microenvironment. C57BL/6J wild type (WT) and Cxcl10 knockout mice (Cxcl10−/−) were treated with diethylnitrosamine (DEN) and tetrachloromethane (CCl4) to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Studies to determine cell–cell communication between macrophages and fibroblasts could help to understand how certain signals promote fibrotic changes and differentiation of subsets of mesenchymal cell populations. For example, the CXCR3-CXCL10 axis modulates the immune cell proportion in tissue in part through the regulation of infiltration, e.g., inhibiting NK cells and anti-tumor T cells [ 29 , 47 ] or promoting neutrophils and macrophages [ 38 , 40 ]. An imbalance in immune cell proportion can favor a microenvironment for fibrosis-related tissue remodeling [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies to determine cell–cell communication between macrophages and fibroblasts could help to understand how certain signals promote fibrotic changes and differentiation of subsets of mesenchymal cell populations. For example, the CXCR3-CXCL10 axis modulates the immune cell proportion in tissue in part through the regulation of infiltration, e.g., inhibiting NK cells and anti-tumor T cells [ 29 , 47 ] or promoting neutrophils and macrophages [ 38 , 40 ]. An imbalance in immune cell proportion can favor a microenvironment for fibrosis-related tissue remodeling [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most interestingly, this difference of soluble chemokine levels between early HCC (defined as BCLC 0/A) compared to cirrhotic control patients remained consistent in four out of nine chemokines (CXCL5, CXCL9, CXCL10, and CXCL11). CXCL10 regulates several hallmarks of the tumor microenvironment and especially modulates the infiltration of anti-tumoral T cells [ 10 ]. CXCL11 was described as a marker of liver injury caused by viral hepatitis [ 22 ] and was even positively associated with development of HCC compared to non-cirrhotic controls in patients with chronic HCV and HBV infection [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent mechanistic studies are providing further insight into the mechanisms of action of individual chemokines. Accordingly, it could be shown that CXCL10 modulates the infiltration of anti-tumorigenic immune cells in HCC while CXCL5 promotes proliferation, migration, and invasion of HCC cells through the activation of PI3K and ERK1/2 signaling pathways with consecutive infiltration of neutrophils [ 9 , 10 ]. In the setting of HCC, previous studies mainly focused on viral induced liver disease and identified serum cytokine profiles that were associated with the risk of carcinogenesis [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These cytokines have been previously related to the progression of chronic liver injury. Intrahepatic CXCL10 has been strongly associated to liver fibrosis in different context in human liver pathologies(46, 47) through regulation of macrophage-associated inflammation(48) or the infiltration of immune T cells. (46) CXCL12, the ligand of CXCR4, can be involved in multiple pathological mechanisms in fibrosis, such as inflammation, immunity, epithelial-mesenchymal transition, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Intrahepatic CXCL10 has been strongly associated to liver fibrosis in different context in human liver pathologies(46, 47) through regulation of macrophage-associated inflammation(48) or the infiltration of immune T cells. (46) CXCL12, the ligand of CXCR4, can be involved in multiple pathological mechanisms in fibrosis, such as inflammation, immunity, epithelial-mesenchymal transition, and angiogenesis. (49) Furthermore, the secretome analysis reflected a role for hepatocytes in producing ECM proteins under the control of the EGFR pathway.…”
Section: Discussionmentioning
confidence: 99%